Forensic characteristics of the offender who committed a criminal offence under Article 206-2 of the Criminal Code of Ukraine (Law and Safety, 2024)
An effective investigation of any criminal offence is not possible without forming a forensic profile, which includes information about the criminal’s identity.The article examines the scientific developments on the issues related to the forensic characteristics of the offender who committed the unlawful seizure of property of an enterprise, institution or organisation.It is determined that information that characterises the identity of the offender may be obtained during the inspection of the scene or as a result of a pre-trial investigation. At the scene of an incident, information about the identity of the offender may be contained in material and ideal traces. During the pre-trial investigation, information is obtained as a result of investigative (detective) actions, covert investigative (detective) actions and other procedural measures.Based on the results of the comprehensive analysis, two main groups of features characterising the identity of the offender who committed the criminal offence under Article 206-2 of the Criminal Code of Ukraine were formed. The first group includes general features that indicate social, demographic, and biological characteristics; the second group includes special features that characterise the personality of the offender from the perspective of the criminal offence committed and describe his or her relationship with the victim, the position held, the state of sanity at the time of the illegal act, the role and place in the criminal group, etc.Based on the study, the classification of raiders available in science is identified, namely: the white, grey, black raiders and greenmailers. Depending on the attitude to the criminal event, the persons are classified as organisers, aware and unaware of the criminal acts.The typical portrait of a criminal is characterised based on the analysis of theoretical developments and empirical material, namely, criminal proceedings under Article 206-2 of the Criminal Code of Ukraine and court decisions thereunder.It has been noted that the purpose of the criminal offences under study is the unlawful seizure of property of an enterprise, institution or organisation through transactions for mercenary, economic, consumer motives, as well as for the purpose of eliminating competitors.
Keywords: criminal proceedings; pre-trial investigation; forensic characteristics; identity of the offender; unlawful seizure; property; raiding.